2001
DOI: 10.3168/jds.s0022-0302(01)70169-5
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nervous System Activity in Adipose Tissues During Pregnancy and Lactation of the Rat

Abstract: The concentration and turnover of norepinephrine in white adipose and liver tissues were determined in pregnant, lactating, and age-matched virgin rats to elucidate the adaptations in sympathetic nervous system activity. In study 1, at d 18 of pregnancy and d 7 and 21 of lactation, animals were killed, and liver and cardiac perimetrial and retroperitoneal adipose depots were quick-frozen and then assayed for norepinephrine as a gross estimate of sympathetic innervation. In study 2, the same design was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 10 publications
7
15
0
Order By: Relevance
“…The changes in these hypothalamic neuropeptides would not only support the orexigenic drive necessary to meet the energy demands of milk production, but would also decrease energy expenditure through suppression of sympathetic tone. The changes in UCP expression that we observed here are consistent with the decrease in sympathetic tone that has been reported during lactation (30).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The changes in these hypothalamic neuropeptides would not only support the orexigenic drive necessary to meet the energy demands of milk production, but would also decrease energy expenditure through suppression of sympathetic tone. The changes in UCP expression that we observed here are consistent with the decrease in sympathetic tone that has been reported during lactation (30).…”
Section: Discussionsupporting
confidence: 94%
“…The mechanism behind the changes in UCP1 and UCP3 could be due to many factors, including the decrease in sympathetic nervous system activity or hormonal changes associated with lactation, i.e. leptin, PRL, and oxytocin (8,9,30).…”
Section: Discussionmentioning
confidence: 99%
“…it requires a much lower insulin concentration) [37]. Sympathetic nervous activity has been described to diminished in retroperitoneal and gonadal WAT with pregnancy [38], in order to save energy for foetal growth and maternal fat storage. Since α 2 -AR has a higher affinity for norepinephrine than β 3 -AR [31,39], in late pregnancy, with lower levels of β 3 -AR and norepinephrine, the decrease of α 2A -AR may be a feedback downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous work by Sumner and McNamara [145] and Bionaz and Loor [16] which reported that adipose lipogenesis in cows during early lactation is primarily regulated through control of gene expression. Expression of key lipolytic enzyme genes (LIPE, PNPLA2, MGLL and ADRB2) followed a similar pattern early in lactation, indicating that the control of lipolysis in the adipose tissue is likely controlled by post-transcriptional events [75,104,153]. Post-transcriptional activation of HSL through simulation of the b-2-adrenergic receptor and the phosphorylation cascade has been shown to be the first step in the beginning of lipolysis and providing fatty acids to the mammary gland and other tissues [75,144].…”
Section: Genes and Key Pathways Regulating Lipid Metabolism In Adiposmentioning
confidence: 99%